Forecasting CBM Production of Mukah Balingian Coalfield, Sarawak, Malaysia. - Irawan, Sonny (Maxwell Science Publication, 2012)
Coal-Bed Methane (CBM) or coal-bed gas is a form of natural gas extracted from coal beds. The term refers to methane adsorbed into the solid matrix of the coal. In order to understand the performance of a CBM reservoir, we need to know the Original Gas in Place, Production Rates and also Recovery Factor. This is mainly on creating a Microsoft Excel ® 2007 with the help of Visual Basic for Application (VBA) based CBM forecast tool. Field data from Mukah-Balingian Coalfield Sarawak is analyzed and forecasted. Original Gas in Place is calculated by multiplying the mass of the coal with the initial gas content of the coal bed. Following from the generated Relative Permeability data, production rates for both water and gas calculated over a specific time range. During the whole production, an abandonment condition which is mainly the pressure will be set by the engineers. Using this abandonment pressure, we can calculate the recovery factor. Using constant values of Langmuir Volume of 714.29 scf/ton, Langmuir Pressure of 1024.5 psia and reference initial pressure of 2000 psia; flowing pressure of 100 psia which is also the abandonment pressure, various range of skin, permeability, initial gas content as well as porosity tested to predict the field performance. Using the range of initial gas content of 86.286-173.36 scf/ton; range of permeability of 1.01e-6 mD to 1010 mD; porosity, with a range of 0.0001 to 0.5%; Skin ranged from-5 to 4, CBM production is forecasted for the range of 5 years.